Clinical and laboratory parameters associated with febrile seizure recurrence within the first 24 h: a ten-year cohort study - Castellazzi, Massimo Luca; La Vecchia, Adriano; Scali, Martina; Agostoni, Carlo; Di Pietro, Giada; Milani, Gregorio Paolo (Frontiers in Pediatrics, 2024)
We assessed clinical and laboratory parameters associated with early recurrence of febrile seizure in patients presenting at the Emergency Department with a first episode.Case series of patients admitted to the emergency department with the first episode of febrile seizure for ten consecutive years. Exclusion criteria were focal features and prolonged duration (>15 minutes).We included 693 patients, 284 (41%) female. Median age of 20 (IQR 15-27) months.Fifty-two (8%) patients had a recurrence within 24 hours. At univariate analysis, patients with recurrent seizures had higher use of antipyretics (88% vs 74%, P =0.03, OR 2.6, 95% CI 1.1-7.7), higher median maximal body temperature (39.3°C, IQR 38.9 -39.9, vs 38.9, IQR 38.4-39.3, P <0.001, OR 2.3, 95% CI 1.5-2.6) and presented with a lower proportion of respiratory tract infections (54% vs 70%, P =0.02) compared to patients without recurrence. A maximal body temperature equal to or higher than 39°C was associated with a higher recurrence (11% vs 4%, P <0.001, OR 2.9, 95% CI 1.6-5.6). Hyponatremia was not associated with a risk of recurrence. The multivariate analysis confirmed a direct association with body temperature (OR 2.3, 95% CI 1.5-3.7, P <0.001), and an inverse association with respiratory tract infections (OR 0.4, 95% CI 0.2-0.9, P =0.01), while antipyretic use was not correlated (OR 1.9, 95% CI 0.8-5.2, P =0.2).Conclusions: High body temperature and respiratory tract infections were (directly and inversely) associated with recurrences. Consideration of these conditions might help for anticipating the probability of recurrence.